Development of a grinding device for producing coal powder-raw materials of coal-water fuel - Kurytnik, I.P.; Khassenov, A.K.; Nussupbekov, U.B.; Karabekova, D.Z.; Nussupbekov, B.R.; Bolatbekova, M. (Archive of Mechanical Engineering, 2022)
This article proposes a method for grinding coal based on the use of the energy of a pulsed shock wave resulting from a spark electric discharge in a liquid. The main purpose of the scientific work is the development of an electric pulse device for producing coal powder, the main component of coal-water fuel. The diameter of the initial coal fraction averaged 3 mm, and the size of the resulting product was 250 m. To achieve this goal, the dependence of the length of a metal rod electrode (positive electrode) on the length and diameter of its insulation is investigated. Various variants of the shape of the base (bottom) of the device acting as a negative electrode are considered, and an effective variant based on the results of coal grinding is proposed. An experimental electric pulse installation is described, the degree of coal grinding is determined depending on the geometric parameters. The optimal characteristics of the obtained coal powder have been established.
Keywords: coal-water fuel installation; electric pulse installation; grinding device; degree of coal grinding; electrode